Effect of TP53 deficiency and KRAS signaling on the bioenergetics of colon cancer cells in response to different substrates: A single cell study - Kealey, James; Düssmann, Heiko; Llorente-Folch, Irene; Niewidok, Natalia; Salvucci, Manuela; Prehn, Jochen H. M.; D’Orsi, Beatrice (Frontiers in Cell and Developmental Biology, 2022)
Metabolic reprogramming is a hallmark of cancer. Somatic mutations in genes involved in oncogenic signaling pathways, including KRAS and TP53, rewire the metabolic machinery in cancer cells. We here set out to determine, at the single cell level, metabolic signatures in human colon cancer cells engineered to express combinations of activating KRAS gene mutations and TP53 gene deletions. Specifically, we explored how somatic mutations in these genes and substrate availability (lactate, glucose, substrate deprivation) from the extracellular microenvironment affect bioenergetic parameters, including cellular ATP, NADH and mitochondrial membrane potential dynamics. Employing cytosolic and mitochondrial FRET-based ATP probes, fluorescent NADH sensors, and the membrane-permeant cationic fluorescent probe TMRM in HCT-116 cells as a model system, we observed that TP53 deletion and KRAS mutations drive a shift in metabolic signatures enabling lactate to become an efficient metabolite to replenish both ATP and NADH following nutrient deprivation. Intriguingly, cytosolic, mitochondrial and overall cellular ATP measurements revealed that, in WT KRAS cells, TP53 deficiency leads to an enhanced ATP production in the presence of extracellular lactate and glucose, and to the greatest increase in ATP following a starvation period. On the other hand, oncogenic KRAS in TP53-deficient cells reversed the alterations in cellular ATP levels. Moreover, cell population measurements of mitochondrial and glycolytic metabolism using a Seahorse analyzer demonstrated that WT KRAS TP53-silenced cells display an increase of the basal respiration and tightly-coupled mitochondria, in the presence of glucose as substrate, compared to TP53 competent cells. Furthermore, cells possessing oncogenic KRAS, independently of TP53 status, showed less pronounced mitochondrial membrane potential changes in response to metabolic nutrients. Furthermore, analysis of cytosolic and mitochondrial NADH levels revealed that the simultaneous presence of TP53 deletion and oncogenic KRAS showed the most pronounced alteration in cytosolic and mitochondrial NADH during metabolic stress. In conclusion, our findings demonstrate how activating KRAS mutation and loss of TP53 remodel cancer metabolism and lead to alterations in bioenergetics under metabolic stress conditions by modulating cellular ATP production, NADH oxidation, mitochondrial respiration and function.